PHYSICO-MECHANICAL AND PHARMACOTECHNOLOGICAL PROPERTIES OF NIMESULIDE FILMS BASED ON MODIFIED POLYSACCHARIDES - Іщенко, Олена; Баула, Ольга; Плаван, Вікторія; Ляшок, Ірина (Technologies and Engineering, 2022)
Purpose. The aim of the research is to study the physico-mechanical and pharmaco-technological properties of nimesulide films based on modified polysaccharides to obtain dosage forms that can provide a prolonged therapeutic effect. Methodology. To evaluate the physical and mechanical properties of films with nimesulide on the basis of modified polysaccharides, the tensile load and flexural elasticity of the films were determined by standard methods. The effect of nimesulide content in the polymer composition on the sorption kinetics of NaCl solution films was investigated by gravimetric method. The kinetics of nimesulide release from films based on carboxymethylated starch and polyvinyl alcohol were determined using the Dissolution Test. Findings. Physico-mechanical properties of films based on modified polysaccharides with nimesulide were studied. It is determined that increasing the content of nimesulide increases the tensile load by 115%, and flexibility is maintained at the number of bends up to 400 times. A study of the kinetics of sorption of saline NaCl films based on carboxymethylated starch and polyvinyl alcohol with nimesulide has shown an increase in swelling of the films by 270% with increasing content of the pharmaceutical ingredient. The obtained films were found to be dosage forms capable of providing therapeutic nimesulide concentrations. The equation for predicting the kinetics of nimesulide release depending on the concentration of API in the film and the time of its use is proposed. Originality. The scientific novelty of the work is to establish the features of the release of nimesulide from films based on the polymer composition of carboxymethylated starch with polyvinyl alcohol. Practical value. The possibility of using films based on carboxymethylated starch with polyvinyl alcohol in the ratio of 50/50 for the pharmaceutical development of transdermal dosage forms with specified pharmacotechnological properties has been established.